2014
DOI: 10.1155/2014/470358
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Patients That Underwent Computed Tomography Pulmonary Angiography with the Prediagnosis of Pulmonary Embolism in the Emergency Department

Abstract: Introduction. The purpose of this study is to analyze the frequency of other diagnoses and findings in patients that were diagnosed with or not diagnosed with PE following the CTPA in the ED and to analyze the relationship between diagnosis and D-dimer. Instrument and Method. This study involves all patients that presented to the ED that underwent CTPA with the prediagnosis of PE. The items considered in this study were their reason for presenting to the ED and pretest clinical risks for PE, D-dimer, and CTPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
2
4
0
2
Order By: Relevance
“…The prevalence of PTE in our study was comparable to that seen in other studies (19.0-24.3%), ( 11 , 20 , 21 , 23 ) but it was higher than that reported by other authors (8.6-9.5%). ( 16 , 18 , 24 ) Factors such as level of clinical suspicion and compliance with guidelines for the investigation of PTE can affect the prevalence rate of the disease.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The prevalence of PTE in our study was comparable to that seen in other studies (19.0-24.3%), ( 11 , 20 , 21 , 23 ) but it was higher than that reported by other authors (8.6-9.5%). ( 16 , 18 , 24 ) Factors such as level of clinical suspicion and compliance with guidelines for the investigation of PTE can affect the prevalence rate of the disease.…”
Section: Discussionsupporting
confidence: 84%
“…( 18 , 21 , 23 ) In our study, the major abnormal findings on the CTA scans that were negative for PTE were atelectasis, pulmonary nodules, pleural effusion, consolidation, and emphysema. Of note is the significant proportion of nodules and micronodules in our study relative to those reported in other studies, ( 16 , 18 , 20 , 23 , 24 ) which might be related to the high prevalence of granulomatous diseases in Brazil. ( 29 ) Such incidental findings, which were not associated with the patient's acute status, often might require further investigation or long-term follow-up.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations